Linking Daily Victimization to Daily Affect Among Adolescents: The Mediating Role of Sleep Quality and Disturbance. - Wang, Wei; Xie, Mingjun; Liu, Zelin; Chen, Huimin; Wu, Xiaoyi; Lin, Danhua (Journal of Youth & Adolescence, 2025)
Bullying victimization is prevalent among adolescents and often linked to emotional problems. Prior studies have been focused on the concurrent or longitudinal associations between bullying victimization and emotional problems, but the daily associations and the underlying mechanisms remain unclear. Implementing daily diary method, the study aimed to examine the links between daily victimization and positive and negative affect as well as the mediating role of sleep quality and disturbance. A total of 265 Chinese adolescents (M = 11.65, SD = 0.74; 32.80% females) participated in this study and completed 7-day daily diaries on bullying victimization (traditional and cyber victimization), sleep quality and disturbance, and affect. As hypothesized, at the between-person level, sleep disturbance mediated the relationships between both traditional and cyber victimization and subsequent negative affect. At the within-person level, sleep quality mediated the pathway between traditional victimization and next-day negative affect; furthermore, sleep disturbance mediated the pathway between traditional victimization and positive affect the following day. These findings highlight the mediating roles of sleep quality and sleep disturbance in the relationships between stressful victimizing experiences and emotional problems and also provide novel insights into these associations.